PENINGKATAN PENGETAHUAN MASYARAKAT TENTANG PENGGUNAAN OBAT FLU DAN BATUK OTC MELALUI EDUKASI LEAFLET - Asniar Pascayantri; Hasnawati; Astrid Indalifiany; Vica Aspadiah (Jurnal SADEWA, 2026)
Self-medication using over-the-counter (OTC) flu and cough medicines remains a widespread practice in the community. However, limited understanding of correct usage, appropriate dosing, and potential adverse effects frequently results in suboptimal and irrational drug use. This community service activity was designed to enhance public awareness regarding the responsible use of OTC flu and cough medicines through a leaflet-based educational intervention. The program was implemented in Ranomeeto Village, employing a structured approach that encompassed preparatory activities, interactive health counseling, leaflet dissemination, and individualized participant consultation. Post-intervention assessment was conducted using a ten-item Likert-scale questionnaire to measure participants' comprehension levels. Findings indicated a mean total score of 4.57 (91.40%), classified within the excellent category. The highest performance was recorded in information clarity and the opportunity for participants to raise questions, whereas relatively lower scores were noted in participants' self-confidence in applying correct medication practices independently. These results suggest that combining leaflet-based education with direct interpersonal communication is an effective strategy for improving community knowledge and fostering rational OTC medicine use, though continued reinforcement is recommended to strengthen participants' practical confidence